2014
DOI: 10.1590/s0080-623420140000700008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of institutionalization on the perception of autonomy and quality of life in old people

Abstract: RESUMENObjetivo: Evaluar la influencia de la institucionalización en la autonomía y la calidad de vida percibida entre ancianos institucionalizados. Método: Estudio casiexperimental (serie temporal interrumpida) y longitudinal. La muestra estuvo compuesta de 104 añosos de tres centros residenciales de Santander, España. A fin de evaluar la calidad de vida y la dependencia fueron utilizadas dos escalas: el Índice de Barthel y el Índice de Lawton. Resultados: Se observó una relación significativa entre la autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Among the individuals in the present study, independent feeding was the capacity with the highest percentage of independence (95%), while bathing was the most dependent category (46.7%), findings corroborated by another study that used the Katz Index 25 . There are reports in literature that identify a clear relationship between institutionalization and a decrease in autonomy and perception of quality of life among the elderly after 12 months of living in the institution 32 …”
Section: Resultsmentioning
confidence: 99%
“…Among the individuals in the present study, independent feeding was the capacity with the highest percentage of independence (95%), while bathing was the most dependent category (46.7%), findings corroborated by another study that used the Katz Index 25 . There are reports in literature that identify a clear relationship between institutionalization and a decrease in autonomy and perception of quality of life among the elderly after 12 months of living in the institution 32 …”
Section: Resultsmentioning
confidence: 99%
“…As to active aging, aiming at evaluating the influence of institutionalization on the autonomy and quality of life perceived among institutionalized older adults, a study (19) had a sample of 104 older adults from three residential centers of Santander, in Spain. The results of the study showed a decline in the autonomy and independence of older adults as the time of institutionalization increased.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, é primordial que, durante sua formação no Curso de Graduação em Enfermagem, lhes sejam transmitidos conhecimentos que os habilitem a atuar junto à pessoa com estomia e sua família. Além disso, a Estomaterapia apresenta-se como uma especialidade que visa à formação de enfermeiros em nível de pós-graduação (22).…”
Section: Discussionunclassified